2011
DOI: 10.1152/ajpheart.00210.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of metabolism by nitric oxide andS-nitrosothiols in endothelial cells

Abstract: S-nitrosation of thiols in key proteins in cell signaling pathways is thought to be an important contributor to nitric oxide (NO)-dependent control of vascular (patho)physiology. Multiple metabolic enzymes are targets of both NO and S-nitrosation, including those involved in glycolysis and oxidative phosphorylation. Thus it is important to understand how these metabolic pathways are integrated by NO-dependent mechanisms. Here, we compared the effects of NO and S-nitrosation on both glycolysis and oxidative pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…No change in basal OCR was observed for the cells over the course of the experiment with any treatments. The lack of effect of NO on basal respiration has been observed in other cells and is likely due to the fact that basal respiration is largely controlled by the availability of ADP, which is low under unstressed conditions, and not by the activity of the target for NO, cytochrome c oxidase (17;27;44;45). After a total of 250 min a mitochondrial profile was established by the sequential addition of inhibitors of oxidative phosphorylation as described previously (46).…”
Section: Resultsmentioning
confidence: 86%
“…No change in basal OCR was observed for the cells over the course of the experiment with any treatments. The lack of effect of NO on basal respiration has been observed in other cells and is likely due to the fact that basal respiration is largely controlled by the availability of ADP, which is low under unstressed conditions, and not by the activity of the target for NO, cytochrome c oxidase (17;27;44;45). After a total of 250 min a mitochondrial profile was established by the sequential addition of inhibitors of oxidative phosphorylation as described previously (46).…”
Section: Resultsmentioning
confidence: 86%
“…We also found that LA increased the mitochondrial antioxidant capacity, and partially restored mitochondrial enzyme activity and increased ATP yield during sepsis in which an excess of NO had been produced [21]. Other investigators have also reported that the exposure of endothelial cells to small molecular S -nitrosothiols significantly down-regulates their mitochondrial function [22]. Therefore, we hypothesized that inflammation-induced excess NO production increases protein S -nitrosylation, which may result in diminished oxidative phosphorylation and decreased energy production in some mitochondrial enzymes.…”
Section: Introductionmentioning
confidence: 70%
“…In fact, studies have demonstrated that NO inhibits glycolytic flux [57]. Along these lines, proteomics and other biochemical analyses have found evidence for S-nitrosylation of glycolysis-related proteins, such as glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and aldolase [47, 58].…”
Section: Tca Cycle Enzymes As Targets Of S-nitrosylationmentioning
confidence: 99%